IMPLEMENTASI PERATURAN BUPATI INDRAGIRI HULU NOMOR 1 TAHUN 2019 DALAM HAL KEBIJAKAN PEMENUHAN SARANA DAN PRASARANA PENGELOLAAN SAMPAH RUMAH TANGGA - Eci Novita Sari; Maria Maya Lestari; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Facilities and infrastructure for waste management are regulated inIndragiri Hulu Regent Regulation Number 1 of 2019 concerning Policies andStrategies for Indargiri Hulu Regency in the Management of Household Waste andWaste Similar to Household Waste. The purpose of writing this thesis is to: First,find out the policy for fulfilling facilities in waste management based on Article 10Paragraph (2) Indragiri Hulu Regent Regulation Number 1 of 2019 concerningPolicies and Strategies for Indargiri Hulu Regency in Managing Household Wasteand Waste Similar to Household Waste. Second, find out the policy for fulfillinginfrastructure in waste management based on Article 10 Paragraph (2) of IndragiriHulu Regent Regulation Number 1 of 2019 concerning Policies and Strategies forIndargiri Hulu Regency in Managing Household Waste and Waste Similar toHousehold Waste. Third, efforts to deal with waste in Indragiri Hulu Regency inmaximizing facilities and infrastructure based on Indragiri Hulu Regent RegulationNumber 1 of 2019 concerning Policies and Strategies for Indragiri Hulu Regencyin Managing Household Waste and Waste Similar to Household Waste.This type of research is sociological juridical research, because theauthor directly conducts research at the location or place of research in order toprovide a complete and clear picture of the problem under study. The researchlocation is Kelayang District, Rakit Kulim District, Lubuk Batu Jaya District,Sungai Lala District, Batang Peranap District, the Indragiri Hulu RegencyEnvironmental Service, the Indragiri Hulu Regency DPRD.From the results of the research problem, there are three main things thatcan be concluded. Author's suggestion, the Office is more active in managing wastein accordance with the Regent's Regulations, as well as conducting socializationwith the sub-district government so that people do not throw garbage where theyshouldn't.Keywords: Implementation- -infrastructure-facilities-Indragiri Hulu